Навчальна оцінка студента у конкурентному середовищі академгрупи - Ізмайлова, К. В. (Ways to Improve Construction Efficiency, 2014)
Іs proposed the making more active of training process by the way of strengthening the justifying factor. With the substantiation of the economic solutions those students obtain the best estimation, whose the versions of the solutions were best according to the totality of the predetermined criterial and limiting indices. Is illuminated the experience of the application of the justified estimations based on the example of economic disciplines in the direction “building”.